PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN RPP KURIKULUM 2013 MELALUI SUPERVISI AKADEMIK DI SMP NEGERI TANJUNGPINANG TAHUN 2018 - Hariyana Safitri (TANJAK, 2021)
This study aims to determine the increase in the ability of teachers in preparing RPP Curriculum 2013 through academic supervision at SMP Negeri 2 Tanjungpinang in 2018. Academic supervision is a model of coaching carried out by principals or supervisors to teachers to help solve problems related to learning activities for quality. learning can be achieved optimally. School action research (PTS) is a type of quantitative research using Comparative Descriptive Analysis by comparing the results of the initial conditions with the results of the first cycle of local level upgrading techniques (In House Training) and the results of the second cycle with private conversation techniques. This research was conducted in two cycles. Academic supervision as a group (In House Training), with the results of the research cycle I RPP Curriculum 2013 made by teachers is still not optimal, it is necessary to carry out further supervision in cycle II, namely the implementation of supervision measures individually (individual conversation). The average result of the teacher's ability to prepare RPP Curriculum 2013 in the initial conditions is 67.38 (sufficient category). The average result of the quality of the lesson plans compiled by the teacher in the first cycle was 75.02 (good category). The increase in the yield of cycle I compared to the initial conditions was 7.64. Meanwhile, the average quality of RPP Curriculum 2013 compiled by the teacher in cycle II was 81.89 (good category). The increase in the yield of cycle II compared to the result of cycle I was 6.37. Keywords: Supervision, Ability, Curriculum 2013